Application of the Sociodrama Learning Model to Optimize Collaboration in Civics Learning - Annisa Luthfi Azzahra; Fathoni, Achmad (LPPM Undiksha, 2023)
The character possessed by an individual is very diverse, but the fact is that the character of each individual is the same, what distinguishes the character of each individual is the more prominent one of the characters compared to other characters in that individual. One type of character that must be instilled in students is cooperation. Collaboration is an activity carried out in groups or working together to obtain the expected results. Cooperation is an important aspect in educating children. Cooperation is very important to be applied to children from an early age because they have an important role in social life. The purpose of this research is to increase student cooperation through the sociodrama method in Civics learning. The type of research used is descriptive qualitative. With data collection techniques observation, interviews, and tests. The data validity technique used is triangulation. Furthermore, the data obtained will be analyzed by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study indicate that there is an increase in cooperation through sociodrama on several components for students such as being active in collaborating between groups, increasing interaction skills, contributing both energy and mind, establishing good relationships between group members, helping group members who experience difficulties. From the results obtained, it can be concluded that the use of the sociodrama method can increase student cooperation through Civics learning.